2020
DOI: 10.5562/cca3640
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Au Film Thiolation and Silane Bonding Onto SiO2 Films Within the Frame of Biosensor Surface Functionalization – an Analysis of Best Practices and Techniques

Abstract: This paper reviews some of the most common surface modification approaches in biosensing based on self-assembled monolayers with a particular focus on Au film thiolation and SiO2 film silanization. Such approaches are routinely used to alter the materials' surface properties towards a desired bioresponse. Furthermore, the most appropriate characterization methods towards ensuring successful surface modification are presented including XPS, HREELS, SPFS, Raman and FTIR spectroscopy as well as UPS with specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The former peak can be deconvoluted to three Si species, namely, Si 2p 1/2 (blue curve), Si 2p 3/2 (red curve), and Si 2 O (green curve) centered at 100, 99.4, and 100.3 eV , binding energies, respectively. The latter broad peak in Figure d can be fitted into two Gaussian curves corresponding to the oxides of the substrates as in SiO 2 bonding at 103 eV , (cyan–blue curve) and the bonding between the organosilane Si and the inorganic silicon dioxide (Si sub –O–Si APTES ) centered at 102 eV (purple curve). ,, Based on our systematic optimization, we found that deposition at a low concentration (0.1%) and short immersion time (30 min) is optimal for yielding a 0.6 nm monolayer of APTES SAM based on ellipsometry measurement (Figure S1). Our result is consistent with both a recent report and the simulated molecular size of APTES obtained from the force fields function­(Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The former peak can be deconvoluted to three Si species, namely, Si 2p 1/2 (blue curve), Si 2p 3/2 (red curve), and Si 2 O (green curve) centered at 100, 99.4, and 100.3 eV , binding energies, respectively. The latter broad peak in Figure d can be fitted into two Gaussian curves corresponding to the oxides of the substrates as in SiO 2 bonding at 103 eV , (cyan–blue curve) and the bonding between the organosilane Si and the inorganic silicon dioxide (Si sub –O–Si APTES ) centered at 102 eV (purple curve). ,, Based on our systematic optimization, we found that deposition at a low concentration (0.1%) and short immersion time (30 min) is optimal for yielding a 0.6 nm monolayer of APTES SAM based on ellipsometry measurement (Figure S1). Our result is consistent with both a recent report and the simulated molecular size of APTES obtained from the force fields function­(Figure S2).…”
Section: Resultsmentioning
confidence: 99%